An exploration of the effects of low-pressure plasma discharge on the physico-chemical properties of chia (Salvia hispanica L.) flour - Rohit Upadhyay; Rohit Thirumdas; Rajendra R. Deshmukh; Uday Annapure; Nrusimha N. Misra (Journal of Engineering & Processing Management, 2019)
This work explores the preliminary feasibility of employing low-pressure cold plasma technology for the modification of the properties of chia flour. Chia flour was exposed to low-pressure plasma in the air for 5 min, 10 min, and 15 min, at two different power levels (40 W and 60 W). The oils extracted from untreated and treated chia flour were exhaustively characterized for fatty acid composition, nutritional value, and rancidity indices using thermal calorimetric methods (DSC/TGA). The results indicated a significant change in the color of flour with an increase in lightness. Infrared and ultraviolet spectroscopy indicated changes in the tocopherol groups of the oil extracted from plasma-treated chia flour. However, the oil extracted from plasma-treated chia flour revealed a loss of conjugated dienes and the formation of trans-fatty acids as seen in conventional hydrogenation of edible oils. DSC and TGA results revealed better oxidative stability of low-pressure plasma-treated oils than in control, which was linked to a relative increase of MUFA in the former.
Keywords: electrical discharge; grains; fatty acid; functional property